Eco-friendly ways for managing insect pests in aonla - Singh, Rudra P; Singh, A K; Singh, R K; Yadav, S K; Singh, R P K (Indian Horticulture, 2018)
Having high nutritive value with medicinal properties, aonla is rated as suitablefruit for delicious processed products for therapeutic use. Its large plantationand commercialization took place which over the time has sheltered many insectpests causing huge economic losses. Many insects have been identified, listedand grouped into sap feeders, defoliators, gall forming insects and borers.Major insects are aphid, aonla bug, mealy bug, hairy caterpillar, leaf roller/twister, shoot gall maker, bark-eating caterpillar and fruit-borer. Since, aonla isgenerally used for health and vitality promotion, eco-friendly management ofinsect pests is needed to avoid residues.